The exogenous form of Jaagsiekte retrovirus is specifically associated with a contagious lung cancer of sheep. - Palmarini, M (1996)
Sheep pulmonary adenomatosis ([SPA] ovine pulmonary carcinoma) is a transmissible lung cancer of sheep that has been associated etiologically with a type D- and B-related retrovirus (jaagsiekte retrovirus (JSRV]). To date it has been impossible to cultivate JSRV in vitro and therefore to demonstrate the etiology of SPA by a classical approach. In addition, the presence of 15 to 20 copies of endogenous JSRV-related sequences (enJSRV) has hampered studies at the molecular level. The aim of this study was to investigate whether the expression of exogenous JSRV was specifically associated with neoplasia in SPA-affected animals. Initially, we found that enJSRVs were transcribed in a wide variety of normal sheep tissues. Then, by sequencing part of the gag gene of enJSRV we established a ScaI restriction site in gag as a molecular marker for the exogenous form of JSRV. Restriction enzyme digestion of PCR products obtained from the amplification of cDNA from a total of 65 tissues collected from SPA-affected and unaffected control sheep revealed that the exogenous form of JSRV was exclusively and consistently present in tumor tissues and lung secretions of the affected animals. In addition, exogenous JSRV provirus was detected only in DNA from SPA tumors and not from nontumor tissues of the same animals. This study has demonstrated clearly that the exogenous form of JSRV is specifically associated with SPA tumors.